Faktor-Faktor Yang Mempengaruhi Keputusan Petani Ikut Serta Asuransi Usaha Tani Padi di Kabupaten Deli Serdang - Gultom, Jontar; Kusuma, Sinar Indra; Ayu, Sri Fajar (Universitas Medan Area, 2025)
The agricultural sector is one of the businesses with high risks and uncertainties. Sources of risk and uncertainty, among others, come from the natural environment, especially climate change, floods, droughts and explosions of plant pest organisms. To overcome the losses of farmers, especially rice farming from the risk of crop failure, the government helps to protect farming businesses in the form of Rice Farming Insurance. This study aims to analyze the factors that influence farmers' decision to participate in rice farming insurance in Deli Serdang regency. The number of samples in this study was 100 samples with purposive sampling technique method. Factors influencing farmers' decision to participate in the rice farming insurance were analyzed using binary logistic regression. The results showed that the farmer's decision to participate in rice farming insurance can be explained by the variables of farmer education, income, number of family dependents, land area, farming experience, intensity of the risk of crop failure, insurance procedures and getting government assistance by 86.8% while the remaining 13.2% is explained by variables outside the model. Internal factors that influence farmers' decisions to participate in the rice farming insurance include land area and farming experience. External factors that influence farmers' decisions to participate in the rice farming insurance include the intenistas of the risk of crop failure, following the insurance program